Leisure in society : a network structural perspective - Stokowski, Patricia A. (Mansell, 1994)
Leisure as an object of sociological inquiry. Traditional approaches in the sociology of leisure. Recent interpretive approaches to leisure. Elements of a structural sociology of leisure. Social networks research. Social networks research in leisure. A critique of leisure networks research. Conclusions and consequences of a structural sociology of leisure.